The inclusion of watermarks based on QR Code analysis - Waleed, Jumana; Saadoon Jasim, Sarah; Abbas, Thekra (International Journal of Engineering and Technology, 2018)
With the quick arrival of high grades of acceptance, the QR Code technology is becoming more adaptable and usable every day by more and more people. Lately, the utilization of two dimensional QR codes for the powerful encoding of information with a big capacity becomes significantly growing; especially for encoding the identity. Because the identity is private information, it requires being further authenticated. This paper firstly works on analyzing the content of the QR Code and finding the unimportant locations inside it; Then, a combination of the digital watermarking concept and QR Code technology is used to substitute the founded unimportant locations by the watermark for the purpose of increasing the authenticity for the owner of the identity. The experimental results show that the inclusion of watermark bits inside the detected unimportant locations did not affect the process of decoding and retrieving information from the QR Code.Â Â